Administrative Detention: Compliance of the Code of Ukraine on Administrative Offenses with Social Needs and the Current State of Keeping Human Rights and Freedoms - M. A. Sambor (Bulletin of Kharkiv National University of Internal Affairs)
The author has studied administrative detention as a measure to ensure proceedings in cases on administrative offenses, its use in documenting administrative offenses and interdependent measures, as well as the use of data obtained as evidence in proceedings in cases on administrative offenses.